Ventilator-Associated Pneumonia: The Role of Emerging Diagnostic Technologies - Kollef, Marin H.; Burnham, Carey-Ann D. (Seminars in Respiratory and Critical Care Medicine, 2017)
Antibiotic resistance has emerged as a key determinant of outcome in patients with serious infections along with the virulence of the underlying pathogen. Within the intensive care unit (ICU) setting, ventilator-associated pneumonia (VAP) is a common nosocomial infection that is frequently caused by multidrug-resistant bacteria. Antimicrobial resistance is a growing challenge in the care of critically ill patients. Escalating rates of antibiotic resistance add substantially to the morbidity, mortality, and cost related to infection in the ICU. Both gram-positive organisms, such as methicillin-resistant Staphylococcus aureus and vancomycin-intermediate S. aureus, and gram-negative bacteria, including Pseudomonas aeruginosa, Acinetobacter species, carbapenem-resistant Enterobacteriaceae, such as the Klebsiella pneumoniae carbapenemase–producing bacteria, and extended spectrum β-lactamase organisms, have contributed to the escalating rates of resistance seen in VAP and other nosocomial infections. The rising rates of antimicrobial resistance have led to the routine empiric administration of broad-spectrum antibiotics even when bacterial infection is not documented. Moreover, there are several new broader-spectrum antibiotics that have recently become available and others scheduled for approval in the near future. The challenge to ICU clinicians is how to most effectively utilize these agents to maximize patient benefits while minimizing further emergence of resistance. Use of rapid diagnostics may hold the key for achieving this important balance. There is an urgent need for integrating the administration of new and existing antibiotics with the emerging rapid diagnostic technologies in a way that is both cost-effective and sustainable for the long run.
Keywords: rapid diagnostics; antibiotic resistance; microbiology; outcomes